PEMBINAAN UKM MUKENAH BORDIR KOTA PARIAMAN UNTUK MENEMBUS PASAR NASIONAL - Sosmiarti Sosmiarti; M. Nazer; Venny Darlis (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
This activity aims to help resolve two Mukenah UKM problems in Kota Pariaman, namely: from the aspect of product production and marketing. From the perspective of production, improving the quality of human resources, and developing motives. In the field of marketing is breaking the long marketing chain through bookkeeping online sales. To achieve the above objectives, the methods that have been carried are Methods of lectures and counseling about the creative economy, the development of product motifs of various forms of Mukenah, and the importance of Entrepreneurship. Next was demonstration and training in making motives, creating new products to support the development of Mukena products that is the form of mukenah bags, prayer mats, and product packaging and bookkeeping. The result of this dedication is Mukenah UKM has gained knowledge about the motivation, models, and completeness of Mukenah according to market demand. UKM can do simple bookkeeping about the activity of buying and selling their products, can already load various colors because the raw material of the fabric is already available in the City of Pariaman. UKM also have trademarks and get consumers online. On the other side, the surrounding community has gained knowledge and embroidery skills that can help Mukenah UKM in increasing production. Government policies are needed to continue the development of products and help superior market products in this area through exhibition events and others. So that embroidery products from the City of Pariaman can penetrate the world market.